Detection of Antibacterial Compound of Avicennia marina Against Pathogens Isolated from Urinary Tract Infected Patients - Sheela Devi1, A.; Rajkumar2, Johanna; Beenish1, T.K. (Asian Journal of Chemistry, 2014)
Medicinal plants have been precious and important sources of natural products for the health of human beings and they have a great potential to produce new drugs. A number of mangroves and its associates possess new agrochemical products and biologically active compounds with medicinal value, which show biological activities such as antimicrobial properties. So they have capacity to treat diseases, because of its curative value. Also they are less toxic to humans and ecofriendly. A urinary tract infection (UTI) is an infection in the urinary tract. It almost certainly affects one-half of all people during their lifetimes. Bacteria are the most frequent cause of urinary tract infections. An antibacterial activity of leaves of Avicennia marina was evaluated against bacteria accountable for urinary tract infection and also antibacterial compound 1,3-benzodioxole,5,5-(tetrahydro-1H,3H-furo [3,4-c]furan-1,4-diyl)bis-,[1s-(1a,3aa,4b,6aa)] was isolated from leaf extract. Hence, the study suggests that A. marina can be used to treat urinary tract infection.